2017
DOI: 10.3996/072016-jfwm-055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Body Composition and Fatty Acid Profiles between Wild and Cultured Rio Grande Silvery Minnows

Abstract: Federally endangered Rio Grande Silvery Minnows (RGSM; Hybognathus amarus) were raised in one of three culture regimes: intensively, with only a hatchery diet; semi-intensively with access to natural food and hatchery diet supplementation; and with only natural food available at the Los Lunas Silvery Minnow Refugium (Los Lunas, New Mexico), a naturalized conservation refugium designed to mimic the natural environment of the RGSM in the Rio Grande. The project compared each culture regime and assessed differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Since 2009, we have observed Rio Grande silvery minnow behavior in the refugium during fish culture projects and the spawning study. We have also observed the fish's behavior when it was raised in fiberglass tanks using production aquaculture management for other projects (Tave et al, 2012;Hutson et al, 2013Hutson et al, , 2017Powell et al, 2017).…”
Section: Methodsmentioning
confidence: 84%
“…Since 2009, we have observed Rio Grande silvery minnow behavior in the refugium during fish culture projects and the spawning study. We have also observed the fish's behavior when it was raised in fiberglass tanks using production aquaculture management for other projects (Tave et al, 2012;Hutson et al, 2013Hutson et al, , 2017Powell et al, 2017).…”
Section: Methodsmentioning
confidence: 84%
“…A proximate analysis of percent body fat showed that Rio Grande Silvery Minnow raised using conservation aquaculture management had the same percent body fat as wild fish, while fish that were fed a formulated ration had a significantly greater percent body fat (Powell et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, only one comparison has been made between fish raised in the refugium and those raised under traditional fish culture management. A proximate analysis of percent body fat showed that Rio Grande Silvery Minnow raised using conservation aquaculture management had the same percent body fat as wild fish, while fish that were fed a formulated ration had a significantly greater percent body fat (Powell et al 2017).…”
Section: Daysmentioning
confidence: 99%
“…Hatchery‐reared Rio Grande Silvery Minnow Hybognathus amarus that were fed a diet of natural prey also had whole‐body lipid levels similar to those of wild fish (Powell et al. ). Liver glycogen was highly variable among wild populations, with relatively high levels in one population compared to the other populations.…”
Section: Discussionmentioning
confidence: 99%
“…; Powell et al. ). Use of live forage may also have other benefits, such as the potential to prepare fish behaviorally for successful foraging in natural conditions (Paszkowski and Olla ; Brown and Laland ; Wintzer and Motta ; Thompson et al.…”
mentioning
confidence: 98%